Pojav znižane meje sneženja na območju doline Planice in Peči (Tromeje) - Strle, Danijela (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2016)
In the paper we analyze the precipitation event on the night from March 25th 2015 to March 26th 2015 during the passage of the cold front. Analysis of temperature conditions in meteorological stations around the studied area (Planica Valley and Mt. Peč) shows that during the precipitation event there was no cold advection under 2500 m. In fact, data showed even small temperature rise. However, during the period of the strongest precipitation, temperatures on our monitoring stations fell close to freezing point and for short period isotherm profile was formed in the Planica Valley. Consequently, snow line reached valley bottom for a few hours. Data also show that during strongest precipitation and cooling, wind speed at the valley bottom decreased to almost calm, which indicates decoupling of air in the lower part of the valley from the air above.
Keywords: climatology; Julian Alps; Julijske Alpe; klimatologija; padavine; Planica; sneg; temperatura; Tromeja